Role of Manual Vacuum Aspiration Versus Sublingual Misoprotol in First Trimester Miscarriage in a Tertiary Care Hospital PMC, Nawabshah - Rashida Akbar, Basma, Rozina Mujeeb Sahito, Raishem Ali, Sonia Gul Qureshi, Saira Parveen Memon (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the efficacy of manual vacuum aspiration versus sublingual misoprostol in first trimester miscarriage at people’s medical college hospital Nawabshah. Study Design: Randomized Controlled Trial. Settings: Department of Gynaecology and Obstetrics, Peoples Medical University & Hospital Nawabshah. Duration of Study: 7th April 2021 to 6th October 2021. Materials & Methods: A total of 100women with first trimester incomplete abortion, 18 to 45 years of age were included. Patients having allergy to misoprostol or other prostaglandins, contraindication to prostaglandin therapy (asthma, hypertension, glaucoma) and suspected ectopic pregnancy assess on ultrasound were excluded. Group A received a single dose of 600 microgram of sublingual misoprostol every three hours and group B who underwent MVA for evacuation of retained products of conception. Efficacy was noted. Results: The mean age of women in group B was 30.14 ± 4.12 years and in group A was 30.20 ± 3.69 years. Majority of the patients 51 (51.0%) were between 18 to 30 years of age. The mean gestational age in group B was 7.92 ± 2.42 weeks and in group A was 7.48 ± 2.32 weeks. In this study, success was seen in 46 (92.0%) women in group B (manual vacuum aspiration) and 37 (74.0%) women in group A (sublingual misoprostol) with p-value of 0.017. Conclusion: This studyconcluded that manual vacuum aspiration (MVA) is effective and safe procedure as compared to sublingual misoprostol in first trimester incomplete abortion.